Strategi Komunikasi Organisasi Ormas LPADKT Dalam Melestarikan Budaya Dayak Di Kota Samarinda - Bang, Fredi Kristian; Sary, Kezia Arum; Juwita, Rina; Kristian, Dony (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to analyze the communication strategies implemented by the LPADKT organization in preserving the existence of Dayak culture. This research uses a qualitative descriptive approach to provide an in-depth description of the communication strategies applied by the Laskar Pemuda Adat Dayak Kalimantan Timur (LPADKT) organization in preserving Dayak culture in the city of Samarinda. Primary data were obtained through interviews with the leaders and bureau heads of LPADKT, while secondary data were gathered from relevant documents and literature. Data analysis was conducted inductively to identify patterns and themes related to communication strategies, cross-cultural dynamics, as well as supporting and inhibiting factors in cultural preservation. The results show that the organizational communication applied by LPADKT in preserving Dayak culture in Samarinda is effective and well-structured. Clarity of messages, appropriate selection of communication channels, and consistent communication frequency, supported by a culture of openness, enable cultural values to be conveyed effectively, especially to the younger generation. The use of social media as a mass communication channel, combined with interpersonal and organizational communication, successfully increases active participation from members and the wider community. Additionally, systematic coordination and constructive conflict management strengthen organizational solidarity, allowing cultural preservation goals to be optimally achieved. Message consistency and high member participation also play key roles in maintaining the continuity of Dayak cultural transmission.